2011
DOI: 10.1598/rrq.46.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning Argumentative Reading and Writing: A Review of Research

Abstract: Acquiring argumentative reading and writing practices reflects a key component of recent curricular reforms in schools and universities throughout the United States and the world as well as a major challenge to teachers of reading and writing in K‐12 and college writing classrooms. In this review, we consider the contributions of two research perspectives, cognitive and social, that researchers have employed in the study of the teaching and learning of argumentative reading and writing. We address two basic qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(40 citation statements)
references
References 140 publications
0
19
0
6
Order By: Relevance
“…The group discussion activities likely helped the students develop knowledge and ideas for their essays. Furthermore, prior research supports dialogic writing activities which provide students the opportunity to consider multiple perspectives, see limitations in their initial point of view, and avoid my-side bias (Coker & Lewis, 2008; Kuhn & Crowell, 2011; Kuhn et al, 1997; Newell et al, 2011; Reznitskaya & Anderson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The group discussion activities likely helped the students develop knowledge and ideas for their essays. Furthermore, prior research supports dialogic writing activities which provide students the opportunity to consider multiple perspectives, see limitations in their initial point of view, and avoid my-side bias (Coker & Lewis, 2008; Kuhn & Crowell, 2011; Kuhn et al, 1997; Newell et al, 2011; Reznitskaya & Anderson, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of article comprehension skills, our conclusions are consistent with other studies (Brosowsky et al, 2020; Sego & Stuart, 2016; Varela et al, 2005; Wenk & Tronsky, 2011) which have demonstrated that using a set of questions to scaffold the reading of research articles helps students to better understand the structure of scientific writing (cf. Madigan et al, 1995; Newell et al, 2011). Taken together with Kershaw et al (2020), our current results suggest that beyond a few practice assignments, more practice is not necessarily better.…”
Section: Discussionmentioning
confidence: 99%
“…Goldman & Bisanz, 2002). In addition, students are often unfamiliar with the basic structure of scientific writing (Newell et al, 2011), which scaffolds readers’ understanding of research (Madigan et al, 1995). Compared to experts, undergraduate students are less likely to utilize strategies such as lowering cognitive load through summarizing and taking notes (Nelms & Segura-Totten, 2019) or to interact with research articles in more complex manners such as critically interpreting data (Hubbard & Dunbar, 2017).…”
mentioning
confidence: 99%
“…Opplaering i argumenterande sakprega skriving − i alle fag − er slik ei viktig side ved skulens samfunnsmandat. Vidare er argumenterande sakprega skriving rekna som ei skrivedidaktisk utfordring, noko som over fleire tiår har fått mykje merksemd i både norsk og internasjonal skriveforsking (Andrews et al 2009;Berge 2005a;Freedman & Pringle 1988;Ferretti & Fan 2016;Hertzberg 2008;Hillocks 2011;Igland 2009;Muller Mirza et al 2009;Newell et al 2011;Skjelten 2013;Øgreid 2017a).…”
Section: Innleiingunclassified